2013
DOI: 10.1016/j.cocis.2013.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Balance of enthalpy and entropy in depletion forces

Abstract: Solutes added to solutions often dramatically impact molecular processes ranging from the suspension or precipitation of colloids to biomolecular associations and protein folding. Here we revisit the origins of the effective attractive interactions that emerge between and within macromolecules immersed in solutions containing cosolutes that are preferentially excluded from the macromolecular interfaces. Until recently, these depletion forces were considered to be entropic in nature, resulting primarily from th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
100
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(115 citation statements)
references
References 72 publications
(87 reference statements)
7
100
0
Order By: Relevance
“…The implications of these enthalpic changes for the mechanism of osmolyte stabilization were pointed out by Politi and Harries (37): There must be other intermolecular forces acting in addition to steric crowding. Sukenik et al categorized possible mechanisms based on the measured sign and relative magnitudes of enthalpic and entropic contributions (38). Senske et al did a similar classification of possible mechanisms for protein stabilization based on observed changes in enthalpy of unfolding and melting temperature T m (which depends also on entropy) (39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The implications of these enthalpic changes for the mechanism of osmolyte stabilization were pointed out by Politi and Harries (37): There must be other intermolecular forces acting in addition to steric crowding. Sukenik et al categorized possible mechanisms based on the measured sign and relative magnitudes of enthalpic and entropic contributions (38). Senske et al did a similar classification of possible mechanisms for protein stabilization based on observed changes in enthalpy of unfolding and melting temperature T m (which depends also on entropy) (39).…”
Section: Discussionmentioning
confidence: 99%
“…The second difficulty is that observed effects of osmolytes and crowders on protein binding and folding often have significant enthalpic contributions (23,(37)(38)(39). Excluded volume effects are entropic, whether treated by the mean-field AO, scaled particle, or HS mixture models.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the relative fibril elongation rate in our simulations with 40 Å crowders has a value that is similar to the relative fibril elongation rate for insulin fibrils in the presence of 200 kDa dextran. Our relative fibril elongation rates for Ab (16)(17)(18)(19)(20)(21)(22) with 20 Å crowders are equivalent to those obtained for bovine insulin and insulin B-chain with 200 kDa dextran, and our relative fibril elongation rates for Ab (16)(17)(18)(19)(20)(21)(22) with 5 Å crowders are equivalent to those obtained for human a-synuclein and hen egg white lysozyme with 200 kDa dextran.…”
Section: Introductionmentioning
confidence: 72%
“…Experiments have been conducted to examine how attractive molecules, including osmolytes (14)(15)(16)(17)(18)(19)(20), saccharides (21), small-molecule inhibitors (22)(23)(24), and quantum dots (25), affect protein aggregation. Among these experimental studies, the most relevant to our work involved the addition of osmolytes to a system of proteins, because they employed concentrations and size scales similar to those used in our simulations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation